Osmoregulation in grouper Epinephelus Coioides (Hamilton) larvae and juveniles. - Caberoy, Nora Blanca
The changes in Na+,K+_ATPase activity, chloride cell morphology, and survival of grouper Epinephelus coioides larvae and juveniles abruptly transffered from ambient rearing conditions (32 ppt, 26.5-30 degrees centigrade) to the different salinity (8, 18, 32, 40 ppt) and temperature (25, 30 degrees centigrade) combinations were determined. In addition, the osmotic response of day 60 juveniles were evaluated under the same test conditions., the response of day 20 larvae to abrupt changes in environmental conditions was found to be influenced by the interaction of temperature and salinity. Na+,K+-ATPase did not vary at salinities 8-32 ppt (1.09{ogon}0.59 - 4.16{ogon}1.03 umol Pi/mg protein/h) regardless of temperature. However, enzyme activity significantly decreased (P<0.01) from 6 to 12 h after exposure to 40 ppt at 25 - 30 degrees centigrade. This sudden drop in Na+,K+- ATPase activity was accompanied by a significant increase (P<0.05) in the density and fractional area of the chloride cells. Survival rates at 40 ppt were significantly lower (0 - 5.6{ogon}2.1%) cmpared to other treatments. Likewise, Na+K+-Atpase activity, and chloride cell morphology in gills of day 40 metamorphic groupers were also affected by the interaction of temperature and salinity. enzyme activity (17.03{ogon}8.98 - 49.24{ogon}12 umol Pi/mg protein/h) was similar in 8-40 ppt at 25 degrees centigrade and 8 and 32 ppt at 30 degrees centigrade throughout the experimental period. A significant decrease (P<0.05) in enzyme activity was observed in 18 and 40 ppt at 30 degrees centigrade at 6 h compared to the initial level. There was a subsequent increased (P<0.05) in Na+,K+-ATpase activity in 40 ppt at 12 h compared to its value 6 h after transfer. This was associated with the increase in density resulting to an increased fractional area but with a decreased individual chloride cell area. Survival rates were similar (P>0.05) but were generally higher in fish exposed to 30 degrees centigrade (71.2{ogon}5.5 - 81.2{ogon}10.9%) than 25degrees centigrade (53.8{ogon}8.7 - 65.1{ogon}12.1%). There were no significant changes in Na+, K+-ATPase activity (22.36{ogon}8.55 - 54.27{ogon}5.51 umol Pi/mg protein/h), chloride cell morphology (cell size: 34.14{ogon}1.62 - 52.01{ogon}2.92 um raise to the second power; density: 32.20{ogon}2.68 - 46.38{ogon}8.32 cells/cm raise to the second power; fractional area: 7.95{ogon}2.87 - 23.62{ogon}2.20%), and survival rates (83.3{ogon}9.6 - 100%) of day 60 E. coioides abruptly transferred to the diffeent test salinities and temperatures. Their plasma osmotic concentrations were also found to be well-regulated, attaining equilibrium state (426{ogon}6 - 457{ogon}4 mmol/kg) after 6-24 regardless of treatment. this lack of changes in response to sudden salinity and temperature transfers indicate that grouper at day 60 have better regulatory capacity and are equipped with highly efficient salt-secreting and ion uptake mechanisms compared to early (day 20) and metamorphic juveniles (day 40). Moreover, grouper larvae and juveniles are efficient osmoregulators over a wide range of salinities. Although physiological response and survival rates of early larvae (day 20) and metamorphic juveniles (day 40) seem to be affected by the interaction temperature and salinity. These development of tolerance limits may reflect their ontogenetic response to actual conditions existing in the natural environment.